A single‐item measure of social identification: Reliability, validity, and utility. (4th November 2012) - Postmes, Tom; Haslam, S. Alexander; Jans, Lise
<x xml:space="preserve">Abstract</x> This paper introduces a single‐item social identification measure (SISI) that involves rating one's agreement with the statement 'I identify with my group (or category)' followed by a 7‐point scale. Three studies provide evidence of the validity (convergent, divergent, and test–retest) of SISI with a broad range of social groups. Overall, the estimated reliability of SISI is good. To address the broader issue of single‐item measure reliability, a meta‐analysis of 16 widely used single‐item measures is reported. The reliability of single‐item scales ranges from low to reasonably high. Compared with this field, reliability of the SISI is high. In general, short measures struggle to achieve acceptable reliability because the constructs they assess are broad and heterogeneous. In the case of social identification, however, the construct appears to be sufficiently homogeneous to be adequately operationalized with a single item.